Genetic assessment of BoLA-DRB3 polymorphisms by comparing Bangladesh, Ethiopian, and Korean cattle - Mandefro, Ayele (J Anim Sci Technol, 2021)
Attributable to their major function in pathogen recognition, the use of bovine leukocyte antigens (BoLA) as disease markers in immunological traits in cattle is well established. However, limited report exists on polymorphism of the BoLA gene in zebu cattle breeds by high resolution typing methods. Thus, we used a polymerase chain reaction sequence-based typing (PCR-SBT) method to sequence exon 2 of the BoLA class II DRB3 gene from 100 animals (Boran, n = 13; Sheko, n = 20; Fogera, n = 16; Horro, n = 19), Hanwoo cattle (n = 18) and Bangladesh Red Chittagong zebu (n = 14). Out of the 59 detected alleles, 43 were already deposited under the Immuno Polymorphism Database for major histocompatibility complex (IPD-MHC) while 16 were unique to this study. Assessment of the level of genetic variability at the population and sequence levels with genetic distance in the breeds considered in this study showed that Zebu breeds had a gene diversity score greater than 0.752, nucleotide diversity score greater than 0.152, and mean number of pairwise differences higher than 14, being very comparable to those investigated for other cattle breeds. Regarding neutrality tests analyzed, we investigated that all the breeds except Hanwoo had an excess number of alleles and could be expected from a recent population expansion or genetic hitchhiking. Howbeit, the observed heterozygosity was not significantly (p < 0.05) higher than the expected heterozygosity. The Hardy Weinberg equilibrium (HWE) analysis revealed non-significant excess of heterozygote animals, indicative of plausible over-dominant selection. The pairwise FST values suggested a low genetic variation among all the breeds (FST = 0.056; p < 0.05), besides the rooting from the evolutionary or domestication history of the cattle. No detached clade was observed in the evolutionary divergence study of the BoLA-DRB3 gene, inferred from the phylogenetic tree based on the maximum likelihood model. The investigation herein indicated the clear differences in BoLA-DRB3 gene variability between African and Asian cattle breeds.